Excerto orquestral para violino do poema sinfônico Don Juan Op. 20 de Richard Strauss: um estudo técnico-interpretativo - Márcio Cecconello (2013)
This work is a study of technical elements and interpretation regarding the orchestral excerpt formed by the first sixty-two bars of the first violin part of Richard Strauss symphonic poem Don Juan Op. 20. Interviews with brazilian professional violinists and conductors and concertmasters of several nationalities allowed us to report an overview of the current practice of orchestral excerpts for violin. They also helped us with specific issues about the performance of this kind of repertoire in the context of orchestral auditions. With the statements and suggestions collected in these interviews and having the works of Rodney Friend and Willian Preucil as main references, guidelines for technical approach andinterpretation of this excerpt were proposed. This proposal resulted in an edition of that excerpt, with the aim of helping violinists to prepare for orchestra auditions.